2018
DOI: 10.1039/c8ce01266k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of core–shell ZIF-67@Co-MOF-74 catalyst with controllable shell thickness and enhanced photocatalytic activity for visible light-driven water oxidation

Abstract: Core–shell ZIF-67@Co-MOF-74 catalysts with improved photocatalytic properties were synthesized via the ligand exchange method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…Core-shell MOFs have been successfully applied in photocatalysis, in which the shell MOF can accumulate/recognize reactants and the core MOF with catalytically active sites can transform the reactants to products. 106,107,159 Kitagawa and coworkers applied MIL-101(Cr)@NH 2 -MIL-125(Ti) in the adsorption-photocatalytic removal of Cr VI (Fig. 12D).…”
Section: Catalysismentioning
confidence: 99%
“…Core-shell MOFs have been successfully applied in photocatalysis, in which the shell MOF can accumulate/recognize reactants and the core MOF with catalytically active sites can transform the reactants to products. 106,107,159 Kitagawa and coworkers applied MIL-101(Cr)@NH 2 -MIL-125(Ti) in the adsorption-photocatalytic removal of Cr VI (Fig. 12D).…”
Section: Catalysismentioning
confidence: 99%
“…Wang et al 38 studied the photocatalytic ability of ZIF-67@Co-MOF-74 for visible-light-driven H 2 O oxidation. They converted ZIF-67 into ZIF-67@Co-MOF-74 via surface ligand exchange from MIM to 2,5-dihydroxyterephthalate (DHTP), which forms hard coordination bonding.…”
Section: Catalysismentioning
confidence: 99%
“…Wang et al 38 . studied the photocatalytic ability of ZIF‐67@Co‐MOF‐74 for visible‐light‐driven H 2 O oxidation.…”
Section: Catalysismentioning
confidence: 99%
“…[ 63 ] As shown in Figure , Guo et al synthesized a ZIF‐67@Co‐MOF‐74 core–shell structure via the SALE. [ 64 ] For ligand participated in the construction of the crystalline framework, bond breakage or ligand exchange reaction may occur by chemical or physical stimuli. [ 65–69 ] Sánchez‐Laínez et al showed that ZIF‐7/8 hybrid core–shell frameworks could be obtained through postsynthetic modification by benzimidazole.…”
Section: Synthetic Approachesmentioning
confidence: 99%